Influence of Reduced Molar Mass of Low-Acyl Gellan Gum on Weak Gel Formation and Rheological Properties - Nina G. Mikusheva; Ivan M. Zorin; Alexander S. Gubarev; Alexandr V. Ievlev; Olga V. Volina; Nikolai V. Tsvetkov (Gels)
Reduced-molar-mass low-acyl gellan gum was obtained by the centrifugation of an aqueous solution of commercially available food-grade gellan gum. The derived sample was characterized by NMR, FTIR, ICPE, and viscometry methods. The characteristics were compared with commercially available gellan gum Gelzan™. The main focus of the investigation is on the rheological properties of low-molar-mass-gellan ion-induced gels and the influence of reduced molar mass on gelling of gellan. The gels were prepared by adding 0.2–0.3 M of NaCl or KCl to the 0.6 g/dL gellan gum aqueous solution in a 1:1 ratio. The kinetics of gelling at room temperature, studied by rheological methods, strongly depends on molar mass and is practically independent of the temperature (up to 37 °C) and the type of ions. Analysis of the mechanical spectra characterized the obtained gels as weak gels. The gelling temperature achieved upon cooling for low-molar-mass gellan with a 0.1 M NaCl concentration was 39.0 °C (rheology) and 43.5–42.5 °C (visual observation). In summary, this study complements the existing knowledge about how the reduced molar mass of low-acyl gellan gum influences its rheological properties and gelling behavior in ion-induced systems and provides insights into the formulation of gellan-based gels, which can be effectively utilized in various food and pharmaceutical applications.